Difference between revisions of "The transpose of a matrix"

From Robotics
Jump to: navigation, search
 
(2 intermediate revisions by the same user not shown)
Line 1: Line 1:
 
{{Navigation|before=[[Multiplication with a scalar]]|overview=[[Matrices]]|next=[[Addition of matrices]]}}
 
{{Navigation|before=[[Multiplication with a scalar]]|overview=[[Matrices]]|next=[[Addition of matrices]]}}
 +
{{Exercise|Selftest: Transpose}}
  
 
The transpose of an m-by-n matrix <math>\mathbf{A}</math> is the n-by-m matrix <math>\mathbf{A}^T</math> where all the colums are written as rows and all the rows as colums: <br/><br/>
 
The transpose of an m-by-n matrix <math>\mathbf{A}</math> is the n-by-m matrix <math>\mathbf{A}^T</math> where all the colums are written as rows and all the rows as colums: <br/><br/>
Line 27: Line 28:
 
   (\mathbf{A} \cdot \mathbf{B})^T        &= \mathbf{B}^T \cdot \mathbf{A}^T\\
 
   (\mathbf{A} \cdot \mathbf{B})^T        &= \mathbf{B}^T \cdot \mathbf{A}^T\\
 
   \left(\mathbf{A}^{-1}\right)^T &= \left(\mathbf{A}^T\right)^{-1}
 
   \left(\mathbf{A}^{-1}\right)^T &= \left(\mathbf{A}^T\right)^{-1}
\end{align}</math><br/><br/>
+
\end{align}</math>
  
 
{{Example
 
{{Example

Latest revision as of 18:03, 13 November 2015

← Back: Multiplication with a scalar Overview: Matrices Next: Addition of matrices

Review.png

There are exercises as selftest for this article.


The transpose of an m-by-n matrix \mathbf{A} is the n-by-m matrix \mathbf{A}^T where all the colums are written as rows and all the rows as colums:


  \mathbf{A}=
  \begin{pmatrix}
    a_{11} & a_{12} & \dots &a_{1n} \\
    a_{21} &\ddots & &\vdots\\
    \vdots & & & \\
    a_{m1} & \dots & &a_{mn}
  \end{pmatrix}, \quad
  \mathbf{A}^T =
  \begin{pmatrix}
    a_{11} & a_{21} & \dots &a_{m1} \\
    a_{12} &\ddots & &\vdots\\
    \vdots & & & \\
    a_{1n} & \dots & &a_{mn}
  \end{pmatrix}

If an n-by-n square matrix is concerned the transpose is obtained by mirroring the matrix at its first diagonal from top left to bottom right.

In general the following arithmetic rules hold:

\begin{align}
  (\mathbf{A}+\mathbf{B})^T &= \mathbf{A}^T + \mathbf{B}^T\\
  (c \cdot \mathbf{A})^T &= c \cdot \mathbf{A}^T\\
  \left(\mathbf{A}^T\right)^T    &= \mathbf{A}\\
  (\mathbf{A} \cdot \mathbf{B})^T         &= \mathbf{B}^T \cdot \mathbf{A}^T\\
  \left(\mathbf{A}^{-1}\right)^T &= \left(\mathbf{A}^T\right)^{-1}
\end{align}
Example: The transpose of a matrix



  \mathbf{A}=
  \begin{pmatrix}
    2 & 3 & 0 \\
    1 & 4 & 2 \\
    5 & 6 & 2
  \end{pmatrix}, \quad
  \mathbf{A}^T =
  \begin{pmatrix}
    2 & 1 & 5 \\
    3 & 4 & 6 \\
    0 & 2 & 2
  \end{pmatrix}